2007
DOI: 10.2174/138161207782023711
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Snake Venom Metalloproteinases in Cell Biology: Effects on Platelets,Inflammatory and Endothelial Cells

Abstract: Snake venom metalloproteinases (SVMPs) are widely distributed in snake venoms and play important roles in hemostatic disorders and local tissue damage that follows snakebite. The impact of SVMPs on hemostasis has been extensively studied showing diverse effects both on soluble factors and cellular components. The action of SVMPs involves catalytic and anti-adhesive properties, as well as direct cellular activation and/or the release of endogenous bioactive components. The purpose of this review is to overview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 98 publications
(150 reference statements)
2
78
0
1
Order By: Relevance
“…The hemorrhagic process triggered in the envenomation is directly related to the degradation of basement membrane, cell surface and plasma proteins due to catalytic properties of SVMPs [22,23]. Baldo and collaborators [57] demonstrated that a particular tissue accumulation of jararhagin in the basement membrane is essential for the damage of the blood vessels and suggested that this accumulation is due to the binding of the toxin to collagen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hemorrhagic process triggered in the envenomation is directly related to the degradation of basement membrane, cell surface and plasma proteins due to catalytic properties of SVMPs [22,23]. Baldo and collaborators [57] demonstrated that a particular tissue accumulation of jararhagin in the basement membrane is essential for the damage of the blood vessels and suggested that this accumulation is due to the binding of the toxin to collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Venom metalloproteinases, particularly PIII-SVMPs, are responsible for the local and systemic hemorrhage and are also involved in the local lesions due to their pro-inflammatory action or the ischemia at the site of the bite which arises from the reduction of blood supply following the damage of microvasculature [22,23]. Fortunately, PIII-SVMPs are highly immunogenic and are the predominant antigens recognized by commercial antivenoms for Bothrops snakes [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all proteolytically active enzymes are able to degrade the vascular matrix and act as hemorrhagins. Different domain structures of the PI-PIV SVMPs, different substrate specificities and other characteristics are controversially discussed to be the molecular landmarks of hemorrhagins which are responsible for the vessel-damaging activity (Escalante et al, 2006;Gutiérrez and Rucavado, 2000;Moura da Silva et al, 2007). Moreover, the concerted action of different venom components, their spatial and temporal distributions around the envenomation site and the dose-dependent, sometimes converse effects of venom components in the different tissues and organ environment will have to be discussed to explain the local tissue damage caused by venoms (recently reviewed by Gutiérrez et al, 2010).…”
Section: Fibrinogen and Beyond: Other Extracellular Matrix Molecules mentioning
confidence: 99%
“…Although the cleavage of laminins, nidogen and other basement membrane constituents can be recapitulated in vitro with the isolated components, the time course is much slower (Baramova et al, 1989;Escalante et al, 2006;Gutiérrez and Rucavado, 2000). Afterwards, additional venom activities synergistically destroy the integrity of the endothelial cell layer (Moura da Silva et al, 2007). Alternatively, endothelial cell-cell contacts, which are mainly mediated by VE-cadherin, are targeted by other venom proteinases (Ohsaka et al, 1975) or by proteolytic digestion products of fibrin (ogen) (Gröger et al, 2009;Petzelbauer et al, 2005).…”
Section: Fibrinogen and Beyond: Other Extracellular Matrix Molecules mentioning
confidence: 99%
“…These local effects have been defined as pain, hemorrhage, edema, myonecrosis and inflammation. The snake venom metalloproteinases (SVMPs) have been considered as playing a crucial role in the development of the local venom-induced pathogenesis (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%